Nature of spiral state and absence of electric polarisation in Sr-doped YBaCuFeO5 revealed by first-principle study - Dibyendu Dey (Nature Portfolio, 2018)
Abstract Experimental results on YBaCuFeO5, in its incommensurate magnetic phase, appear to disagree on its ferroelectric response. Ambiguity exists on the nature of the spiral magnetic state too. Using first-principles density functional theory (DFT) calculations for the parent compound within LSDA + U + SO approximation, we reveal the nature of spiral state. The helical spiral is found to be more stable below the transition temperature as spins prefer to lie in ab plane. Dzyaloshinskii-Moriya (DM) interaction turns out to be negligibly small and the spin current mechanism is not valid in the helical spiral state, ruling out an electric polarisation from either. These results are in very good agreement with the recent, high quality, single-crystal data. We also investigate the magnetic transition in YBa1−xSrxCuFeO5 for the entire range (0 ≤ x ≤ 1) of doping. The exchange interactions are estimated as a function of doping and a quantum Monte Carlo (QMC) calculation on an effective spin Hamiltonian shows that the paramagnetic to commensurate phase transition temperature increases with doping till x = 0.5 and decreases beyond. These observations are consistent with experimental findings.